Erythritol as a Next-Generation Sweetener: properties, metabolism, cardiovascular risk and gut health implications – A literature review - Skowrońska-Borsuk, Julia; Narożniak, Martyna; Pękacka, Adrianna Ewa; Czerwiec, Bartłomiej; Borsuk, Adam; Pergoł, Joanna Katarzyna; Wojtas, Malwina; Borkowska, Julia; Krupa, Zuzanna; Sposób, Julia (Quality in Sport, 2025)
Introduction and Purpose: The global epidemic of metabolic diseases has prompted a growing interest in modifying dietary habits. Sucrose, a commonly used sweetener, is ubiquitous in food products, contributing to its excessive global consumption. Due to its numerous drawbacks there is increasing demand for low-calorie sugar substitutes in human nutrition. Among the most frequently selected sugar substitutes is erythritol, a four-carbon polyol that is industrially produced through the fermentation of glucose by yeast. The aim of this study is to highlight the key characteristics of erythritol, examine its potential adverse effects, evaluate its advantages among other polyols, discuss its possible health-promoting properties, impact on the gut microbiota, and identify directions for future research. Material and methods: The review was is based on the thorough analysis of the materials selected from PubMed, Scopus, Google Scholar and Science Direct using the following key words: erythritol, erythritol metabolism, gut microbiota, polyols, non-nutritive sweeteners, butyric acid. Conclusions: Erythritol is a well-tolerated, low-calorie sugar alcohol with minimal systemic metabolism and negligible impact on blood glucose levels. It is largely absorbed in the small intestine and excreted unchanged, with limited fermentation in the colon. While human studies show no significant impact on gut microbiota, ex vivo findings suggest a potential for increased production of beneficial short-chain fatty acids. Recent observational studies have raised concerns about potential associations with cardiovascular risk. However, these findings are inconclusive and require further investigation. Emerging animal data indicate erythritol may modulate gut epithelial structure via microbiota-derived metabolites. Overall, erythritol remains a promising sugar substitute, but its long-term health effects warrant additional high-quality clinical research.